On pairwise super continuous multifunctions - Bouseliana, Hend M.; Kilicman, Adem (AIP Publishing LLC, 2013)
The aim of this paper is to present the notation of pairwise upper super continuous multifunction in bitopological spaces. The basic properties and characterizations of such multifunctions are established.